2004
DOI: 10.1021/ci0341262
|View full text |Cite
|
Sign up to set email alerts
|

Encoding the Core Electrons with Graph Concepts

Abstract: The core electron problem of atoms in chemical graph studies has always been considered as a minor problem. Usually, chemical graphs had to encode just a small set of second row atoms, i.e., C, N, O, and F, thus, graph and, in some cases, pseudograph concepts were enough to "graph" encode the molecules at hand. Molecular connectivity theory, together with its side-branch the electrotopological state, introduced two "ad hoc" algorithms for the core electrons of higher-row atoms based, mainly, on quantum concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…The choice of a K 7 for iodine is based on the fact that, to date, only odd complete graphs, K p with p = 1, 3, 5, 7, 9 have been successful in QSPR studies. The K p representation for the core electrons allows us to define the following general algorithm for δ v 1–6: Parameter p · r equals the sum of all vertex degrees in a complete graph. The handshaking theorem states that this sum for every type of graph, and pseudo‐graphs, complete graphs inclusive, equals twice the number of connections 21, 22.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The choice of a K 7 for iodine is based on the fact that, to date, only odd complete graphs, K p with p = 1, 3, 5, 7, 9 have been successful in QSPR studies. The K p representation for the core electrons allows us to define the following general algorithm for δ v 1–6: Parameter p · r equals the sum of all vertex degrees in a complete graph. The handshaking theorem states that this sum for every type of graph, and pseudo‐graphs, complete graphs inclusive, equals twice the number of connections 21, 22.…”
Section: Methodsmentioning
confidence: 99%
“…This choice would introduce K 2 vertices for n = 2 atoms, thus redefining all graphs made up of second‐row atoms. Previous work 1–6 has shown that in Eq. (1), q = 1, and p , even if other values cannot be excluded a priori.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations